Increasing the Brand Awareness of Toko Makmur Raya’s Target Market Through a Promotional Video - Sugiarto Surya Otto (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Toko Makmur Raya is a paint shop located in Makassar. The store's target markets are forepersons, house owners, and developers. Those three frequently visit the store and become loyal customers of the store. As one of the biggest stores in Makassar, Toko Makmur Raya has problem. That Toko Makmur Raya does not have strong branding to attract the target market. Therefore, Toko Makmur Raya needs to increase its brand awareness. To make that happen, the author provides a solution which is a promotional video. The theory of branding, target market, Unique Selling Point (USP), promotion, and promotional video will be used to make it happen. After finding out three USPs of the store that is: complete, affordable, and excellent services, those were highlighted in the promotional video. A promotional video can benefit the store because it can reach a larger audience by uploading the video to social platforms. Keywords: promotional video, brand awareness, target market, private store